2007
DOI: 10.1097/00005082-200703000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Coping and Depressive Symptoms in Adults Living With Heart Failure

Abstract: Individuals who used more planful problem-solving and social support seeking coping strategies had fewer depressive symptoms, whereas individuals who used more escape-avoidance coping (eg, wishful thinking) had more depressive symptoms. When demographic factors also were included in a regression analysis assessing depressive symptoms, marital status, functional impairment, and the coping strategies of planful problem-solving and escape-avoidance were all statistically significant predictors of depression. Sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 20 publications
2
72
2
Order By: Relevance
“…16,28 The strategy of planful problem solving was also found to be associated with less depression. 26 Problem-focused strategies, however, were not found to be significantly associated with less depression in the other studies. 24,25,27 Although not statistically significant, it was found that participants who were high users of active behavioral coping showed less depression than did participants who used active behavioral coping less.…”
Section: Problem-focused Copingmentioning
confidence: 64%
See 4 more Smart Citations
“…16,28 The strategy of planful problem solving was also found to be associated with less depression. 26 Problem-focused strategies, however, were not found to be significantly associated with less depression in the other studies. 24,25,27 Although not statistically significant, it was found that participants who were high users of active behavioral coping showed less depression than did participants who used active behavioral coping less.…”
Section: Problem-focused Copingmentioning
confidence: 64%
“…Single wave data collection is a convenient method for both the researcher and the participant. Vollman et al 26 investigated the relationships between depression and coping in heart failure patients (n = 75) by administering verbal questionnaires. The participants included a convenience sample selected from a heart institute and ranged in age from 27 to 82 years (mean [SD], 54.6 [13.1] years).…”
Section: Cross-sectional Designsmentioning
confidence: 99%
See 3 more Smart Citations